Transport and metabolism of flavonoids from Chinese herbal remedy Xiaochaihu-tang across human intestinal Caco-2 cell monolayers - Dai Jie-yu; Yang Jun-ling; Li Chuan (Acta Pharmacologica Sinica; Vol 29, No 9 (September 2008): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the limiting factors for oral bioavailability of flavonoids derived from the Chinese herbal remedy Xiaochaihu-tang. The investigational flavonoids included baicalin, wogonoside, oroxylin-A 7-O-β-D-glucopyranosiduronide, liquiritin, liquiritin apioside, isoliquiritin, and isoliquiritin apioside, as well as their aglycones baicalein, wogonin, oroxylin-A, liquiritigenin, and isoliquiritigenin. Methods: Caco-2 cell monolayers were used and the apparent permeability both in apical to basolateral and basolateral to apical directions was measured for each investigational compound. Meanwhile, chemoinformatics was carried out to provide insight into the mechanism governing the permeability. In addition, carrier-mediated transport with or without inhibitors, as well as the metabolism by conjugation, was also examined with Caco-2 cell monolayers for the flavonoids. Results: The investigational flavonoid aglycones exhibited favorable membrane permeability, but efficient glucuronidation and/or sulfation by the enterocytes may limit their bioavailability. For the flavonoid glycosides, their poor membrane permeability was found to be caused by high hydrogen-bonding potential. Among the glycosides, oroxylin-A 7-O-β-D-glucopyranosiduronide, isoliquiritin, and isoliquiritin apioside were transported under the mediation of the efflux transporters multidrug resistance-associated protein and/or P-glycoprotein. Conclusion: The limiting factors of oral bioavailability for the flavonoids derived from Xiaochaihu-tang appeared to include poor membrane permeability, significant efflux, and efficient intestinal metabolism by conjugation.